Oxford handbook of clinical surgery - McLatchie, Greg R.; Leaper, David J. (Oxford University Press, 2002)
This edition provides an overview of the principles, techniques and procedures of surgery. The coverage includes, the assessment and preparation of the patient; anaesthesia; inflammation; general surgical practice; and surgical specialties.